ANALISIS BEBAN KERJA MELALUI METODE FULL TIME EQUIVALENT UNTUK MENGOPTIMALKAN KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA MADIUN - Alvissa Injavira (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
The purpose of this study is to find out the large workload obtained by employees and the optimal number of employees needs in each section and field in the Population and Civil Registry Office of Madiun City. This study was conducted on employees of the Population and Civil Registry Office of Madiun City with a sample of 41 respondents. In addition, this study uses the Full Time Equivalent Method. The result of this study is that employees in the Staffing and General Section have an FTE value of 0.5 (underload) and in the formation only need six employees. Then employees in the Finance Section have an FTE value of 0.5 (underload) and in that section only need two employees. Employees in the Field of Civil Service and Registration have an FTE value of 1.29 (overload) and in that field need to be added two employees. Employees in the Field of Population Registration Services have an FTE value of 1.4 (overload) and need to be added five employees to fill the formation. Employees in the Field of Information Management of Population Administration and Data Utilization have an FTE value of 0.7 (underload) and in that field only need three employees.